"It's just part of life": African American daughters caring for parents with dementia. (3rd March 2020) - McLennon, Susan M.; Anderson, Joel G.; Epps, Fayron; Rose, Karen M.
ABSTRACT: The purpose of this study was to gain a greater understanding of the experiences of African American daughters caring for parents with Alzheimer's disease or a related dementia (ADRD). In this secondary analysis of a subset ( N = 12) of the sample from a previous study, daughters averaged 54 years of age and were caring for parents with moderate to severe ADRD. Results revealed two main categories: Caregiver Concerns and Caregiver Coping. Subcategories included challenging behaviors, social aspects, integration, and family culture and values. Findings offer insight into cultural factors relevant to practice along with research recommendations.